Insights on acetate-ethanol fermentation by hydrogen-producing Ethanoligenens under acetic acid accumulation based on quantitative proteomics. (August 2019) - Li, Huahua; Mei, Xiaoxue; Liu, Bingfeng; Li, Zhen; Wang, Baichen; Ren, Nanqi; Xing, Defeng
Abstract: Ethanoligenens, a novel ethanologenic hydrogen-producing genus, is a representative fermenter in its unique acetate-ethanol fermentation and physiology. Acetic acid accumulation is one of major factors that affect H2 -ethanol co-production. However, sufficient information is unavailable on the tolerance mechanisms of hydrogen-producing bacterium in acetic acid stress. The fermentation process of Ethanoligenens harbinense YUAN-3 was significantly slowed down in the selection stress of exogenous acetic acid. The maximum gas production rate of strain YUAN-3 decreased from 192.15 mL·(L-culture) −1 ·h −1 to 75.2 mL·(L-culture) −1 ·h −1 with increasing exogenous acetic acid from 0 mM to 30 mM, the batch fermentation period was correspondingly expanded from 66 h to 136 h. Through iTRAQ-based quantitative proteomic approach, 78, 121 and 216 proteins were differentially expressed after strain YUAN-3 was cultured in the medium supplemented with exogenous acetic acid of 10 mM, 20 mM and 30 mM. The up-regulated proteins were mainly involved in β-alanine and pyrimidine metabolism, oxidative stress response, while the down-regulated proteins mainly participated in phosphotransferase system (PTS), fructose and mannose metabolism, phosphate uptake, ribosome, and flagellar assembly. These proteins help to maintain balance between fermentation process and alleviation of intracellular acidification in strain YUAN-3. The study indicated that response to acetic acid stress in strain YUAN-3 was a complex process, which involved multiple metabolic pathways. Reductive pyrimidine catabolic pathway played an important role in the acetic acid resistance of E. harbinense . Graphical abstract: Unlabelled Image Highlights: Acetic acid stress slows down fermentation process of Ethanoligenens harbinense 277 proteins of strain YUAN-3 were differentially expressed in acetic acid stress Molecular response to acetic acid stress involves multiple metabolic pathways Reductive pyrimidine catabolic pathway is important in acetic acid resistance